Rock-art image in Fern Cave, Lava Beds National Monument, California : not the AD 1054 (Crab Nebula) supernova - Armitage, R. A.; Hyman, M.; Southon, J.; Barat, C.; Rowe, M. W.
The visual manifestation of the recent Hale-Bopp comet reminds us how telling are those rare objects which suddenly flare in the sky. One can suppose ancient people living by natural light were more compellingly struck by the sight of comets and supernovae, and understandably researchers seek images of them in the shapes of rock-art motifs. An absolute dating contradicts that supposition in respect of a presumed image of the visible supernova of AD 1054.